Antihypoxic Activities of Hibiscus rosa sinensis in Mice - Mohammad hossein Hosseinzadeh; Mohammad Ali Ebrahimzadeh (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Imbalance between low oxygen supply and oxygen demand determines organ hypoxia. It occurs especially in heart diseases and ischemia and causes death. Compounds with antioxidant activity could exhibit antihypoxic properties. Hibiscus rosa sinensis has good antioxidant activity, but there is no information about the antihypoxic activities of this plant. This study was designed to evaluate antihypoxic activities of H. rosa extract. Materials and methods: Protective effects of the methanolic extract of H. rosa against hypoxia-induced lethality in mice were evaluated by experimental models of hypoxia i.e. asphyctic, haemic, and circulatory models. This experimental study was carried out in 15 groups of male mice (n= 6 per group). Data analysis was done applying Analysis of variance and Tukey's multiple comparisons test. Results: Findings showed significant protective activities in all three models. Antihypoxic activity was considerably high in asphyctic and haemic models. In asphyctic model, the extract at 125 mg/kg showed similar activity to positive control, phenytoin (P>0.05), but at 250 mg/kg it was stronger than phenytoin (P<0.05). In haemic model, the extract demonstrated similar activity to propranolol at 125 mg/kg (P>0.05) and greater protective activity at 250 mg/kg (P<0.001). In circulatory model, the H. rosa extract was found to be effective at 62.5 mg/kg (P<0.05). At 125 mg/kg it significantly prolonged survival time to 14.04 ± 1.36 vs 11.37 ± 1.53 min in control group (P<0.01). The extract at 250 mg/kg showed the same activity as propranolol (P>0.05). Conclusion: H. rosa extract showed strong protective effects against hypoxia in all three tested models. Compared to the control group, the extract significantly prolonged survival time in a dose dependent manner.